Adaptive Streaming Protocol (ASP) a routing protocol for live media streams - Dytioco, Jesse Ann (2007)
This research designs a network routing protocol (Adaptive Streaming Protocol) for live multimedia streaming in a peer-to-peer network. Real-time Transport Protocol (RTP), used in multi-party network applications, is referenced in designing the data packets and network flow. The modified packet design includes embedded metadata that allows the network to adapt to heavy traffic through real-time network tuning. It also checks for packet loss and data integrity. Adaptive Steaming Protocol (ASP) was tested against different file sizes, file types and transmission rates. For text files of any size, 0.055% packet loss percentage was reported. On the other hand, a packet loss percentage was reported. On the other hand, a packet loss percentage of 25% was observed for image and movie files. Likewise, the network can withstand transmission of multimedia files for at least 30 minutes.